Capital Structure Determinants of Shariah-Compliant Firms: Evidence from the MENA Region - Abdessamad Raghibi; Lahsen Oubdi (al-Uqud : Journal of Islamic Economics, 2021)
Capital structure choice is vital in corporate financial management due to its effect on both investors' risk and return. Despite the various research that has investigated factors affecting the capital structure of companies, only a few studies have started to examine the capital structure of Shari'ah-compliant companies, especially in the MENA region. Indeed, the screening requirements for which shari'ah-compliant must adhere can affect their capital structure determinants. Hence, under those conditions, this study aims to determine the factors influencing the capital structure of a shari'ah-compliant listed firm in five MENA region countries. The importance of investigating shariah-complaint companies capital structure emanates from the financial constraints on their debt capital structure. Accordingly, this study utilizes static panel data techniques on a sample consisting of Shari'ah-compliant firms over the period 20102018. The findings of this study were consistent with several previous studies as well as the theoretical background of capital structure determinants mainly, the trade-off and the pecking order theory. Our results give insight to managers on what determines their capital structure under shari'ah screening methodologies. However, more insight can be drought from the capital structure of shari'ah-compliant firms by extending the research into industry specifics.